PENGARUH DISIPLIN DAN MASA KERJA TERHADAP LOYALITAS KERJA DENGAN RELIGIUS SEBAGAI VARIABEL MODERASI(STUDY KASUS PADA KARYAWAN PT MISWAK UTAMA) - Ninik Churniawati (Institut Teknologi dan Bisnis Yadika, 2021)
This research is about the Influence of Discipline and Working Period on Religious Work Loyalty as a Moderation Variable (Case Study in Employees of PT Miswak Utama). The Issues Raised From This Study Are To Test Whether There Is a Disciplinary Influence On Work Loyalty, Working Period On Work Loyalty, Testing Whether Religiosity Is Able to Moderate The Influence of Discipline On Loyalty And Mguji Whether Religiosity Is Able to Moderate the Influence of Working Life On Loyalty. Population and Sample In This Study Are Employees of Pt Miswak Utama Number 77. The results showed that discipline and working life have a significant effect on job loyalty, while religiosity does not moderate the effect of discipline on loyalty and religiosity does not moderate the effect of working life on loyalty. So it can be concluded that relisiusity is not a guideline that can increase employee loyalty.